An inside job: To get on the right career track, look within - Singapore Management University (Institutional Knowledge at Singapore Management University, 2012)
Many people may dream about becoming a doctor, but only a few can join the profession. Candidates to the job must not only possess exceptional academic ability, but also, the physical and psychological stamina for typically long, intense shifts that involve giving comfort to the unwell.